Versatile lightweight key distribution for big data privacy in vehicular ad hoc networks. (3rd July 2015) - Qin, Bo; Wang, Linxiao; Wang, Yujue; Wu, Qianhong; Shi, Wenchang; Liang, Bin
Summary: Vehicular ad hoc networks (VANETs) continually produce large scale of data shared among vehicles nearby to improve driving experience and safety. The vehicular communications contain a large amount of private information. It is well known that group key management is a fundamental cryptographic primitive for providing secure group communication. Although many proposals with regard to group key management have been introduced, they cannot well support secure subgroup and intergroup communications in VANETs. In this paper, we exploit the specific features of vehicular communications and propose two group key distribution schemes providing efficient solutions to these two problems. Our schemes do not require interaction between users. Storage and computation analyses show that compared with existing schemes, our proposals are more efficient and versatile. Based on these basic schemes, we present extensions for multipartite groups, by which the efficiency is greatly improved in this scenario. We also provide the extensions for two‐level multipartite groups, which enable fine‐grained real‐world applications. The experimental results confirm that our group key distribution schemes are practical in security, computation, and communication. Copyright © 2015 John Wiley & Sons, Ltd.